EMOTIONAL INTELLIGENCE AND PERFORMANCE : BIBLIOMETRIC ANALYSIS - Readi, Robbi; Sopiah, Sopiah (Universitas Nusa Cendana, 2025)
This article uses a systematic literature review, which aims to summarize several studies regarding emotional intelligence and performance. Emotional intelligence is a factor in the performance of every company. This article uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method and bibliometric analysis using VOSviewer software. Data sources were obtained from ScienceDirect, Emerald Insight, and Taylor & Francis for the 2019-2024 period. The results obtained were 144,195 articles; then data reduction was carried out using exclusive and inclusive criteria to obtain 52 journals that were reviewed. Results for variables related to emotional intelligence and performance, job performance, project performance, team performance, self-efficacy, self-awareness, leadership, etc. Overall, the author hopes that this research can be used as learning material and written reflection in future research. Keywords: Emotional Intelligence; Performance; Prisma; Bibliometric